Motivasi dalam Perspektif Hadis: Studi Kontekstual terhadap Hadis tentang Niat - Tasbih, Tasbih; Saidah (Al-Irsyad Al-Nafs : Jurnal Bimbingan dan Penyuluhan Islam, 2024)
The hadith concerning intention has profound relevance in cultivating motivation, particularly within the realm of Islamic guidance and counseling. This hadith affirms that the value of deeds is contingent upon intention, which serves as the primary impetus for human action. This research contextually analyzes the relationship between intention and motivation, highlighting its role in fostering genuine enthusiasm for achieving noble life goals. In Islamic counseling, sincere intentions form the foundation of a client's motivation to confront life challenges through a spiritual approach. The integration of intention and motivation provides guidance for education, worship, and daily problem solving. By strengthening intentions, a client's motivation becomes more robust, sustainable, and oriented towards Islamic values. This research concludes that a contextual understanding of the hadith of intention is crucial for developing motivation that is not only productive but also imbued with spiritual significance, fostering a meaningful life in both this world and the hereafter.